Optimization of Carotenoid Extraction from Yellow Passion Fruit Pomace Using Ultrasound-assisted Extraction and Coconut Oil as a Solvent - Paramita Dyah Pratiwi; Andriati Ningrum; Supriyadi Supriyadi (Indonesian Food and Nutrition Progress, 2023)
Passion fruit pomace, a by-product of passion fruit juice processing, is a source of carotenoids that can be utilized for food products as an antioxidant. The purpose of this study was to determine the optimum condition of carotenoid extraction process from passion fruit pomace using ultrasonic waves with coconut oil as a solvent, to determine the physicochemical properties of carotene-enriched coconut oil and the physicochemical properties of carotene-enriched coconut oil blended with sesame oil. The variables studied were extraction time (X1) and extraction temperature (X2). Response Surface Methodology (RSM) with the design of Central Composite Face-centered Design (CCF) is used to obtain a mathematical model that corresponds to the relationship between total carotenoid and the variables that influence it. After that, coconut oil will be evaluated on its quality including total carotenoids and antioxidant activity, compared to extraction with conventional methods (maceration). Sesame oil was blended with the carotene-enriched coconut oil extract to improve its antioxidant stability. The results showed that the optimum condition of the yellow passion fruit pomace carotenoid extraction with ultrasound-assisted extraction was 30 minutes and at 35 °C. Characteristics of carotenoid-enriched coconut oil from ultrasound-assisted extraction had higher total carotenoid content (15.79 μg of carotenoids/g oil) compared to conventional extraction (9.47 μg of carotenoids/g oil) and had higher antioxidant activity (80%RSA). Characteristics of mixed oils between carotenoid-enriched coconut oil and sesame oil have higher peroxide, lower Oxidative Stability Index, and higher antioxidant activity.